دور العلاقات العامة في تسيير الصحف الرياضية - بلعربي, صلاح الدين; د.جوادي, صفاء (My University, 2022)
من خلال ما تقدم في هذه الدراسة ومن النتائج التي تم التوصل إليها، لا بدّ من الإعتراف أنّ الصحافة ليست مثالية إلى ذلك الحد، لكنّ تحقيق التوازن بين العلاقات العامة والصحافة هو أمر يفيد الشركات والمؤسسات الإخبارية على حدّ سواء، وعند اختلال التوازن بالعلاقة، يصبح من الصعب أن يثق الجمهور بالأخبار، وهذا يؤدي إلى اعتماد شركات العلاقات العامّة على طرق أخرى للتسويق قد تتسبب بتراجع الثقة بشكل أكبر. لذا نجد أن دور العلاقات العامة في تسيير الصحف الرياضية على غرار باقي الصحف والمؤسسات تعزز الثقة بينها وبين الجمهور من جهة، كما تساعد في تحسين الخدمات من جهة أخرى عنوان الدراسة :هل تلعب العلاقات العامة دورا في تسيير الصحف الرياضية؟ Through the foregoing in this study and the results that have been reached, it must be recognized that the press is not perfect to that extent, but achieving a balance between public relations and the press is something that benefits companies and news organizations alike, and when the relationship is imbalanced, it becomes It is difficult for the public to trust the news, and this leads to PR companies relying on other marketing methods that may cause a further decline in trust. Therefore, we find that the role of public relations in running sports newspapers, similar to other newspapers and institutions, enhances trust between them and the public on the one hand, and also helps in improving services on the other hand. Study title: Does public relations play a role in running sports newspapers? Objectives of the study : - Identify the extent of public relations contribution to the management of sports newspapers. - Identifying the relationship between public relations and its management of sports newspapers. Knowing the extent of public relations contribution to consolidating the relationship between sports newspapers and the public. Study problem: - Does public relations play a role in running sports newspapers? Study hypotheses: General premise: - Public relations play a role in running sports newspapers. Partial hypotheses: Public relations contribute to the running of sports newspapers. - There is a relationship between public relations and its management of sports newspapers. - Public relations contribute to consolidating the relationship between sports newspapers and the public. The method used in the study: The method is considered one of the basic elements and important means that should be available in any study. The research methods used. Tools used in the study:. In our study, we relied on the questionnaire, which we divided into 3 axes as follows: The first axis: Public relations contribute to the management of sports newspapers. The second axis: There is a relationship between public relations and its management of sports newspapers. The third axis: Public relations contribute to strengthening the relationship between sports newspapers and the public. Keywords: public relations, management, sports newspapers. أهداف الدراسة : - التعرف على مدى مساهمة العلاقات العامة في تسيير الصحف الرياضية. - التعرف على العلاقة بين العلاقات العامة وتسييرها للصحف الرياضية. - معرفة مدى مساهمة العلاقات العامة في توطيد العلاقة بين الصحف الرياضية والجمهور. مشكلة الدراسة :- هل تلعب العلاقات العامة دورا في تسيير الصحف الرياضية؟ فرضيات الدراسة : الفرضية العامة: - تلعب العلاقات العامة دورا في تسيير الصحف الرياضية. الفرضيات الجزئية: - تساهم العلاقات العامة في تسيير الصحف الرياضية. - هناك علاقة بين العلاقات العامة وتسييرها للصحف الرياضية. - تساهم العلاقات العامة في توطيد العلاقة بين الصحف الرياضية الجمهور. المنهج المتبع في الدراسة :يعتبر المنهج من العناصر الاساسية والوسائل الهامة التي ينبغي أن تتوفر في أي دراسة، ومن غير المعقول أن يخلوا أي بحث علمي من منهج عن طريقه يصل الباحث إلى التحقق من صحة الفرضيات أو بطلانها، وبهذا تم اعتماد المنهج الوصفي الذي يصنف ضمن مناهج البحث المتبعة. الأدوات المستخدمة في الدراسة :.لقد اعتمدنا في دراستنا على الاستبيان والذي قسمناه إلى 3 محاور كالتالي: المحور الاول: تساهم العلاقات العامة في تسيير الصحف الرياضية. المحور الثاني: هناك علاقة بين العلاقات العامة وتسييرها للصحف الرياضية. المحور الثالث: تساهم العلاقات العامة في توطيد العلاقة بين الصحف الرياضية والجمهور
Keywords: العلاقات العامة; التسيير; الصحف الرياضية